2022
DOI: 10.3390/nu14214662
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Behavior and Diet Interventions among Structural Firefighters: A Narrative Review

Abstract: Structural firefighters (SFFs) are exposed to multiple occupational hazards that affect dietary behavior and can contribute to increased risks of cancer and cardiovascular disease compared to the United States’ general population. Dietary behavior is a feasible modification for positive health outcomes. The objectives of this narrative review are to summarize the diet behavior of SFFs, review findings of diet interventions that positively modify diet behavior, identify research gaps, and suggest recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Epidemiological studies observed that firefighters have a high consumption of red meat and fast food [74,75]. Similarly, fat, cholesterol, protein, sugar, and sodium were overconsumed, whereas fruits, vegetables, grains, and dietary fibers were below recommended levels [61,76]. Evidence from surveys shows that the Mediterranean diet could be the most appealing healthy diet option accepted by many firefighters [58], and is consistent with revised US government dietary guidelines [58].…”
Section: Nutritionmentioning
confidence: 77%
See 1 more Smart Citation
“…Epidemiological studies observed that firefighters have a high consumption of red meat and fast food [74,75]. Similarly, fat, cholesterol, protein, sugar, and sodium were overconsumed, whereas fruits, vegetables, grains, and dietary fibers were below recommended levels [61,76]. Evidence from surveys shows that the Mediterranean diet could be the most appealing healthy diet option accepted by many firefighters [58], and is consistent with revised US government dietary guidelines [58].…”
Section: Nutritionmentioning
confidence: 77%
“…They are often influenced by their colleagues. Hence, counseling and followup were often found to be effective [61]. Moreover, cultural barriers and challenges that might be faced when implementing nutrition intervention programs among firefighters should be carefully evaluated.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Few nutritional interventions within workplace settings have targeted firefighter populations . A recent randomized clinical trial among 137 San Diego firefighters with 24-hour shifts, the Healthy Heroes Study, demonstrated the feasibility of a Mediterranean diet with a self-selected 10-hour time-restricted eating window for 12 weeks and benefit on very LDL particle size (−1.10 nm; 95% CI, −2.16 to −0.03) compared with a standard of care arm.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 One strength was engaging the firefighters in both their work and home environments, given that 80% of representative firefighters previously reported their spouse's opinion/support was important for healthy eating, whereas almost one-third of weekly meals were consumed at the firehouse. 19,28 Given the team setting has shown a greater influence on interventions focused on improving firefighter diet and eating together at the firehouse has been positively associated with benefits unique to the workplace, 43,50 the evaluation specifically considered habits both in the firehouse and at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation